Freemium Business Model: The Darkside of free stuff - Muhamad Idaham, Umar (Faculty of Computer Systems and Software, 2013)
In-app purchasing was introduced to the market during the early 2010. The definition of the term in-application (or in-app) is activities or transactions that are being done within the application. The definition of the word purchase is to acquire (something) by paying for it. The term of “in-application purchase” are digital goods which, when bought from within an app, often either unlock new features, enable the user to skip mundane tasks or provide additional content. In-app purchase is closely related with the term Freemium. The origin of the term Freemium is a combination of the words "ʺfree"ʺ and "ʺpremium"ʺ used to describe a business model that offers both free and premium services.